Pengaruh Media Tanam Ampas Kelapa Terhadap Pertumbuhan Jamur Tiram Putih (Pleurotus Ostreatus) - Rengganis, Dewi; Elfrida, Elfrida; Setyoko, Setyoko (Multiverse: Open Multidisciplinary Journal, 2023)
This study examines the impact of using coconut pulp as a nutrient source in the growing media for white oyster mushrooms (Pleurotus Ostreatus). The objective is to determine the optimal treatment for mushroom growth. Experimental methods, including planting media preparation, seed planting, plot layout, media packaging, sterilization, inoculation, incubation, fruiting body growth, and maintenance until harvest, were employed. Five treatments (P0, P1, P2, P3, P4) with four replications were tested using the Kruskal-Wallis test. The results revealed that the lowest fungal growth occurred at a dose of 90 g (P1), while the highest growth was observed at a dose of 100 g (P3). The Kruskal-Wallis test confirmed significant differences among treatments (Fcount > Ftable, 174313.17 > 9.49, p < 0.05). The highest final pileus diameter was 20.5 cm, and the lowest was 4.5 cm. These findings suggest that the addition of coconut pulp has a noticeable effect on the growth of white oyster mushrooms.